2015
DOI: 10.1037/fam0000096
|View full text |Cite
|
Sign up to set email alerts
|

Holding back, intimacy, and psychological and relationship outcomes among couples coping with prostate cancer.

Abstract: The present study evaluated intimacy as a mechanism for the effects of holding back sharing concerns about cancer on couples' psychological distress, well-being, and marital satisfaction using the actor-partner interdependence model (APIM), and evaluated 2 possible moderators of these associations: the number of patient and spouse cancer concerns. We had 139 men treated for localized prostate cancer in the past year and their spouses complete surveys about holding back sharing cancer concerns, intimacy, distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 43 publications
9
88
0
Order By: Relevance
“…Accordingly, lower perception of empathy from the spouse, lower intimacy, and greater perception of avoidant behaviors and criticism from the spouse are associated with higher levels of holding back from talking about cancer‐related concerns . Notably, whereas 1 study reported lower levels of holding back among female spouses, another reported greater levels of holding back among female spouses, than among their male partners …”
Section: Introductionmentioning
confidence: 82%
“…Accordingly, lower perception of empathy from the spouse, lower intimacy, and greater perception of avoidant behaviors and criticism from the spouse are associated with higher levels of holding back from talking about cancer‐related concerns . Notably, whereas 1 study reported lower levels of holding back among female spouses, another reported greater levels of holding back among female spouses, than among their male partners …”
Section: Introductionmentioning
confidence: 82%
“…Partners report sexual dissatisfaction (Garos, Kluck, & Aronoff, 2007) and poorer relationship communication (Manne, Badr, Zaider, Nelson, & Kissane, 2010). Constructive marital communication is associated with better patient and spouse quality of life and marital satisfaction (Badr & Taylor, 2009;Manne et al, 2010Manne et al, , 2015Song et al, 2012). Despite its importance, some couples struggle to communicate (Badr & Taylor, 2009;Haun, Sklenarova, Brechtel, Herzog, & Hartmann, 2014;Manne et al, 2010Manne et al, , 2015.…”
mentioning
confidence: 99%
“…Constructive marital communication is associated with better patient and spouse quality of life and marital satisfaction (Badr & Taylor, 2009;Manne et al, 2010Manne et al, , 2015Song et al, 2012). Despite its importance, some couples struggle to communicate (Badr & Taylor, 2009;Haun, Sklenarova, Brechtel, Herzog, & Hartmann, 2014;Manne et al, 2010Manne et al, , 2015. Avoiding discussion of cancerrelated concerns, particularly sexuality and worries about the future, is relatively common in this population (Manne et al, 2015).…”
mentioning
confidence: 99%
“…As noted, the marital relationship between patients with prostate cancer and their spouses has been widely studied in European countries and in the United States (Couper et al., ; Hamilton, Van Dam, & Wassersug, ; Harden et al., ; Manne et al., ; Merz et al., ; Tran et al., ; Wittmann et al., ; Zhou et al., ); such research has rarely been conducted in Asian countries. In this regard, in different cultures, couples have different social role expectations.…”
Section: Introductionmentioning
confidence: 99%